2019
DOI: 10.1111/exsy.12402
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and reducing “hospital‐acquired infections” using a knowledge‐based e‐surveillance system

Abstract: The use of automated computer methods when detecting hospital‐acquired infections (HAIs) enhances the validity of the surveillance in an effective manner. This is because manual infection control systems used by hospitals are time consuming and are often restricted to intensive care units. This paper proposes a new knowledge‐based electronic surveillance system to predict and reduce HAIs. The system can gather patient‐associated data from hospital databanks to automatically predict patient injury based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To use the patients’ data more efficiently and detect HAIs sooner, one study integrated multimedia with a simulator system to process patient records automatically to diagnose and predict CLABSI. This automatic surveillance system helps to reduce the CLABSI rate, and 87% optimization was achieved (compared with traditional prevention) (Noaman et al., 2020 ). Four studies showed that using machine learning and deep learning in imaging data and vital signs data was accurate to diagnose tuberculosis and detect sepsis earlier, reducing antibiotic use and antibiotic duration and improving patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To use the patients’ data more efficiently and detect HAIs sooner, one study integrated multimedia with a simulator system to process patient records automatically to diagnose and predict CLABSI. This automatic surveillance system helps to reduce the CLABSI rate, and 87% optimization was achieved (compared with traditional prevention) (Noaman et al., 2020 ). Four studies showed that using machine learning and deep learning in imaging data and vital signs data was accurate to diagnose tuberculosis and detect sepsis earlier, reducing antibiotic use and antibiotic duration and improving patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this method is its ease of understanding and implementation, but it requires experts to develop the rule base. The work of [ 30 ] proposes a knowledge-based system that could automatically extract patient data and output possible injury based on knowledge rules on common central line-associated bloodstream infection. The article [ 31 ] discusses the development of a rule-based classification system for healthcare-associated bloodstream infections (HABSI) to improve patient safety and infection control.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefits of information technology support in IPC practices, there are still several shortcomings that need to be addressed. First, there is a lack of timely response and user-friendly information systems at the system quality level, with system failure being the most common problem [ 8 , 9 ]. Second, at the level of information quality, the data are scattered across multiple systems, resulting in low-quality information lacking integrity and readability that cannot support analysis and decision-making [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few large-scale comprehensive evaluation studies on the application of IPCISs. The theoretical support of the evaluation is weak, and there is a lack of empirical evidence, especially evaluation evidence from direct user clinicians [ 9 , 26 ].…”
Section: Introductionmentioning
confidence: 99%